Increasing The Economic Scale of MSMEs through Islamic-Based Financial Management Literacy In Kedah Malaysia: Peningkatkan Skala Ekonomi UMKM Melalui Literasi Pengelolaan Keuangan Berbasis Syariah Di Kedah Malaysia - Isti Jumro amina; Siska, Siska; Abdullah Chik, Norlaila Abdullah Chik; Nursida, Nina Nursida; Gani, Aulia Gani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
One of the common problems faced by MSMEs is ineffective and efficient financial management. Many MSME owners experience obstacles in budgeting, monitoring cash flow, and controlling expenses. As a result, the sustainability and growth of MSMEs are hampered and may even fail. Therefore, efforts are needed to improve the understanding and financial management skills of MSMEs to support sustainable business growth. To overcome this problem, literacy on MSME financial management was held which was followed by MSMEs in Mukim Singkir Village, Yan Kedah. This activity is a community service cooperation between Universitas Islam Riau and University Utara Malaysia. The methods used are exposure to literacy materials, simple practice, and case discussion. The results obtained were an increase in participants' understanding and skills related to financial management which included: Financial recording, budgeting, cash flow monitoring, accounts payable and receivable management, financial analysis, and cost and expenditure control.